A Study on Dielectric Properties of The Cellulose Derivative-NH4Br-Glycerol- Based The Solid Polymer Electrolyte System - N. M. J., Rasali; Saifful Kamaluddin, Muzakir; A. S., Samsudin (DRPM Universitas Indonesia, 2017)
The characterization of biopolymer-based solid polymer electrolytes (SPEs) has been carried out in this present work. Cellulose derivative was chosen due to its superior physical attributes. In this work, NH4Br-doped glycerol plasticized carboxyl methylcellulose-based SPEs were successfully prepared via the solution casting method. The conductivity and dielectric properties of the prepared films were investigated using the impedance analysis which presented ~1.91×10-3 Scm-1 (with addition of 6 wt% of glycerol). In addition, the studied SPE system shows a non-Debye behaviour without a single relaxation time. The findings of the research indicate that the complexes of NH4Br and glycerol in the cellulose derivative influence the ionic conductivity and dielectric properties of the SPE system.